Recyclable elastic super-ion conductor material, preparation method and application thereof, composite solid electrolyte and lithium battery
By using polymer substrates of elastic and nonelastic phases and functional plasticizers, solid electrolytes with high elasticity, high mechanical strength and high ionic conductivity are prepared, which solves the problem of dendrites and interface contact failure during the circulation of lithium-ion batteries, improves the safety and cycle life of the battery, and supports multiple recycling and reuse.
Patent Information
- Application Number
- CN202510361059.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-26
- Publication Date
- 2025-06-17
AI Technical Summary
Existing lithium-ion batteries are prone to dendrites during circulation, resulting in short-circuit or explosion of the battery, and polymer solid electrolytes are prone to plastic deformation when the volume of the negative electrode changes, resulting in interface stress concentration and contact failure.
A solid electrolyte with strong mechanical and elastic properties is prepared by electrospinning, blending and in-situ spraying methods, etc. Functional plasticizers are introduced to improve the ionic conductivity and mechanical strength of the electrolyte.
It realizes a solid electrolyte with high elasticity, high mechanical strength and high ionic conductivity, effectively inhibits dendrite growth, reduces interface impedance, improves the safety and cycle life of the battery, and supports multiple recycling and reuse of the battery.
Smart Images

Figure CN120164659A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and particularly relates to a recyclable elastic superionic conductor material, a preparation method and application thereof, a composite solid electrolyte, and a lithium battery. Background Art
[0002] With the increasing performance requirements of portable devices, electric vehicles, and grid energy storage applications, lithium-ion batteries have developed rapidly in the past few decades, but have reached the theoretical limit of energy density. Metallic lithium has become the primary choice to replace intercalation anodes such as graphite due to its low electrode potential and high energy density. Unfortunately, traditional liquid lithium metal batteries are prone to dendrite formation during cycling, and the dendrites penetrate the separator, causing battery short circuits or even explosions, facing serious safety risks.
[0003] Solid electrolytes are considered the most promising alternatives to liquid electrolytes due to their non-flammable, non-leaking, high energy density, high mechanical strength, and other multiple performance advantages. Compared with inorganic solid electrolytes with high brittleness and poor interfacial contact, polymer electrolytes have good flexibility and interfacial contact performance, which can alleviate interfacial problems to a certain extent. However, common polymers such as polyethylene oxide (PEO) have a low elastic modulus and cannot adapt to the volume change of the negative electrode during cycling, easily causing plastic deformation, resulting in interfacial stress concentration and contact failure. At the same time, the poor mechanical strength of polymer electrolytes leads to dendritic problems, and the interfacial problems become more serious, damaging the battery cycling performance. Composite solid electrolytes can achieve a synergistic improvement in the elasticity and mechanical properties of the electrolyte by combining two or more polymer phases / inorganic phases, and different components play their respective advantages.
[0004] In addition, the recycling of polymer solid electrolytes is an important issue in the sustainable and environmentally friendly battery industry. Compared with non-recyclable electrolytes, the core advantage lies in its good resource recycling ability and environmental friendliness. Recyclable polymer electrolytes will promote the closed-loop cycle of the battery industry chain, reduce long-term production costs, promote the large-scale application of green energy technologies, and provide important support for global resource security and the low-carbon economic transformation.
[0005] Currently, there is an urgent need in the art to develop a recyclable electrolyte material with high elasticity and high mechanical strength. Summary of the Invention
[0006] The purpose of the present invention is to overcome the problems existing in the prior art, and provide a recyclable elastic superionic conductor material, a preparation method and application thereof, a composite solid electrolyte, and a lithium battery.
[0007] In particular, the present invention utilizes two or more elastic phases / inelastic phases, and through methods such as electrospinning, blending, and in-situ spraying, prepares a special-structured solid electrolyte with strong mechanical properties and elastic properties. While introducing a functional plasticizer to increase the number of charge carriers in the electrolyte and construct a high-speed ion transport pathway, it ensures the dynamic and close contact between the electrolyte and the electrode during the cycling process, promotes the rapid ion interface transport, and effectively inhibits the dendrite problem caused by uneven potential and uneven deposition, obtaining a solid electrolyte with high elasticity, high mechanical strength, and high ionic conductivity. This electrolyte can be applied to the construction of metal anode batteries with high energy density, and can also be used as a separator or electrolyte component of fuel cells, flexible batteries, etc.
[0008] To achieve the above object, in the first aspect of the present invention, a recyclable elastic superionic conductor material is provided, wherein the superionic conductor material includes a polymer substrate and a functional plasticizer doped in the polymer substrate;
[0009] Wherein, the polymer substrate includes an elastic phase and an inelastic phase, and the elastic phase and the inelastic phase are structurally independent of each other.
[0010] In the second aspect of the present invention, a preparation method of the superionic conductor material according to the first aspect is provided, wherein the method is selected from at least two of electrospinning, blending, and in-situ spraying.
[0011] In the third aspect of the present invention, an application of the superionic conductor material according to the first aspect in preparing a separator, a solid electrolyte, or a binder in a metal battery, a secondary ion battery, a flexible battery, a capacitor, or a hybrid energy storage device is provided.
[0012] In the fourth aspect of the present invention, a solid electrolyte membrane made of the superionic conductor material according to the first aspect is provided.
[0013] In the fifth aspect of the present invention, a lithium battery including the solid electrolyte membrane according to the fourth aspect is provided.
[0014] Through the above technical solutions, the beneficial technical effects obtained by the present invention are as follows:
[0015] (1) The present invention selects polymers with intrinsically excellent elastic properties and polymer / inorganic materials with strong mechanical properties as the polymer substrate components, laying a foundation for a superionic conductor material with high elasticity and high mechanical strength. During the cycling process, it is not easy to produce plastic deformation with the change of the anode volume, ensuring the long-term stable compatibility of the interface and effectively inhibiting dendrite growth.
[0016] (2) The present invention provides a recyclable elastic superionic conductor with a special structure, which significantly improves the ionic conductivity, mechanical strength, and interfacial stability through structural innovation. These structures can optimize the ionic transport path, effectively inhibit dendrite growth, reduce the interfacial impedance, and improve the safety and cycle life of the battery.
[0017] (3) By introducing a functional plasticizer, the present invention provides additional high-speed ionic transport channels while reducing the crystallinity of the polymer matrix, further promoting ionic transport and improving the ionic transport efficiency. In addition, the plasticizer is generally an organic small molecule with good compatibility with the polymer matrix, and will not cause additional interfacial problems.
[0018] (4) The composite solid electrolyte membrane prepared from the superionic conductor material of the present invention simultaneously has the advantages of high elasticity, high ionic conductivity, and high mechanical strength. The assembled battery has a low overpotential, a high specific capacity, and excellent cycle performance.
[0019] (5) The composite solid electrolyte membrane prepared from the superionic conductor material of the present invention can be recycled, and the performance of the battery assembled for the second time is still excellent compared with that of the first assembly. The superionic conductor material of the present invention can be applied to metal batteries, secondary ion batteries, flexible batteries, capacitors, or hybrid energy storage devices, etc., and at the same time has good resource recycling ability and environmental friendliness. Description of the Drawings
[0020] Figure 1 It is a cross-sectional scanning electron microscope image of the superionic conductor material prepared in Example 1 of the present invention;
[0021] Figure 2 It is an Arrhenius curve graph of the superionic conductor material prepared in Example 1 of the present invention;
[0022] Figure 3 It is a stress-strain curve graph of the superionic conductor material prepared in Example 1 of the present invention;
[0023] Figure 4 It is a nanoindentation curve graph of the superionic conductor material prepared in Example 1 of the present invention;
[0024] Figure 5 It is a puncture test curve graph of the superionic conductor material prepared in Example 1 of the present invention;
[0025] Figure 6 It is a long cycle performance graph of a lithium metal symmetric battery assembled with the superionic conductor material prepared in Example 1 of the present invention;
[0026] Figure 7Cycling performance graph of the all-solid-state battery assembled with the superionic conductor material, lithium metal anode, and lithium iron phosphate cathode prepared in Example 1 of the present invention at a current density of 0.5C;
[0027] Figure 8 Ionic conductivity curve graph of the superionic conductor material prepared in Example 1 of the present invention after secondary recycling;
[0028] Figure 9 Long-term cycling performance graph of the lithium metal symmetric battery assembled with the superionic conductor material prepared in Example 1 of the present invention after secondary recycling;
[0029] Figure 10 Cycling performance graph of the all-solid-state battery assembled with the superionic conductor material prepared in Example 1 of the present invention after secondary recycling, lithium metal anode, and lithium iron phosphate cathode at 0.5C. Detailed implementation manners
[0030] The endpoints and any values within the ranges disclosed herein are not limited to the exact ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, between the endpoint values of each range and individual point values, and between individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed herein.
[0031] The first aspect of the present invention provides a recyclable elastic superionic conductor material, wherein the superionic conductor material includes a polymer matrix and a functional plasticizer doped in the polymer matrix;
[0032] Wherein, the polymer matrix includes an elastic phase and an inelastic phase, and the elastic phase and the inelastic phase are structurally independent of each other.
[0033] In the present invention, an elastic phase polymer and an inelastic phase polymer / inorganic material are used to form a polymer matrix. Different components play their respective advantages, providing the superionic conductor with excellent mechanical properties and elastic properties, thus bringing better ability to adapt to the volume fluctuation of the anode and the ability to inhibit dendrites, effectively maintaining the long-term stable compatibility of the electrode / electrolyte interface, facilitating the continuous transmission and uniform deposition of interface ions. In addition, the use of a functional plasticizer can effectively improve the dissociation of metal ion salts, facilitate increasing the proportion of amorphous state in the polymer matrix, prepare conditions for the movement of chain segments, and its lithium-conducting groups also provide a high-speed channel for ion transport, thereby synergistically improving the ionic conductivity of the material.
[0034] When the inelastic phase is a polymer or inorganic material with lithium-conducting groups, in addition to bringing its own mechanical strength to the superionic conductor, it provides an additional ion transport path, further enhancing the comprehensive performance of the recyclable elastic superionic conductor.
[0035] For solid-state electrolytes, the advantage of the independent rather than uniformly mixed elastic and inelastic phases is that the phase separation can give full play to the respective advantages of the two phases, avoiding performance degradation caused by uniform mixing or local performance differences caused by non-uniform mixing. As a result, the electrolyte exhibits more excellent performance in aspects such as ion transport, interface stability compatibility, and dendrite growth inhibition, effectively improving the comprehensive performance of the electrolyte.
[0036] In some embodiments of the present invention, the structure of the polymer substrate is selected from at least one of a symmetric or asymmetric multilayer structure, a coaxial nanofiber network structure, and a 3D crosslinked network structure.
[0037] In the present invention, the "symmetric or asymmetric multilayer structure" is a structure in which the composition or property function is symmetric or asymmetric in spatial distribution. A symmetric multilayer is a structure with the same composition or function on both sides, and an asymmetric multilayer structure is a structure with different compositions or functions on both sides, such as a high ion transport layer on one side and a mechanical strength layer on the other side, or the electrolyte is designed as a gradient as a whole; the "coaxial nanofiber network structure" refers to a network prepared by electrospinning technology or in-situ polymerization technology of nanofibers with a core-shell structure, and different materials are used for the inner core and the outer shell, endowing the fibers with multiple functions; the "3D crosslinked network structure" refers to a stable network structure formed by the mutual connection of multiple polymer fibers in three-dimensional space through chemical bonds or physical interactions, having high strength, high elasticity, and good stability.
[0038] In some embodiments of the present invention, in the symmetric or asymmetric multilayer structure, the elastic and inelastic phases are located in different layers, preferably with inelastic phase material layers arranged on both sides of the elastic phase material layer.
[0039] In some embodiments of the present invention, the coaxial nanofiber network structure is coated with an elastic phase material on the fiber network formed by the inelastic phase.
[0040] In some embodiments of the present invention, the 3D crosslinked network structure is formed by hot pressing alternately stacked inelastic phase fiber networks and elastic phase fiber networks.
[0041] In some embodiments of the present invention, the elastic phase is selected from at least one of thermoplastic elastomers and thermosetting elastomers.
[0042] In some embodiments of the present invention, the thermoplastic elastomer is selected from at least one of styrene-isoprene block copolymers, vulcanized rubber, thermoplastic polyurethane elastomers, ethylene-octene copolymers, polybutylene terephthalate, polyamide elastomers, and polyvinyl chloride-based thermoplastic elastomers, preferably vulcanized rubber and / or thermoplastic polyurethane elastomers.
[0043] In some embodiments of the present invention, the thermosetting elastomer is selected from at least one of natural rubber, isoprene rubber, polybutadiene rubber, styrene-butadiene rubber, nitrile rubber, and chloroprene rubber, and preferably at least one of polybutadiene rubber, styrene-butadiene rubber, and nitrile rubber.
[0044] As the substrate of the polymer electrolyte, the elastomer has many performance advantages. Its high elasticity and flexibility can effectively adapt to the volume change during the charge and discharge process of the battery, reduce mechanical stress, and improve the cycle stability of the battery; its good interfacial compatibility can form close contact with the electrode material, reduce the interfacial impedance, and maintain normal ion transport and interfacial transport; its excellent processability and controllability make it easy to optimize performance through molecular design to meet different requirements.
[0045] In some embodiments of the present invention, the non-elastomeric phase is selected from at least one of traditional inorganic fillers, new inorganic fillers, or ordinary non-elastomeric polymers.
[0046] In some embodiments of the present invention, the traditional inorganic filler is selected from at least one of silica, alumina, titanium dioxide, zirconium dioxide, LLZO, LLTO, LATP, and LGPS, and preferably at least one of silica, alumina, titanium dioxide, zirconium dioxide, and LLZO.
[0047] In some embodiments of the present invention, the new inorganic filler is selected from at least one of graphene oxide, carbon quantum dots, lithium-doped basic calcium phosphate, ZIF-90-NH2, and CN@LLZTO, and preferably graphene oxide and / or lithium-doped basic calcium phosphate.
[0048] In some embodiments of the present invention, the ordinary non-elastomeric polymer is selected from at least one of polyethylene oxide, polyacrylonitrile, polycarbonate ethylene, polymethyl methacrylate, and polyvinylidene fluoride, and preferably polyethylene oxide and / or polyvinylidene fluoride-hexafluoropropylene.
[0049] As the substrate of the polymer electrolyte, the non-elastomeric phase also has many performance advantages. Its rigidity and structural stability can provide good mechanical support, prevent the electrolyte from deforming or cracking during the charge and discharge process, thereby extending the battery life; it usually has a high degree of crystallinity, which can effectively inhibit dendrite growth and improve the safety of the battery; the high ionic conductivity can be achieved by regulating the molecular structure, further improving the electrochemical performance of the electrolyte.
[0050] In some embodiments of the present invention, the functional plasticizer is selected from at least one of carbonate plasticizers, ether plasticizers, sulfone plasticizers, and ionic liquid plasticizers.
[0051] In some embodiments of the present invention, the carbonate plasticizer is selected from at least one of ethylene carbonate, propylene carbonate, methyltrifluoroethyl carbonate, dimethyl carbonate, and diethyl carbonate, and is preferably ethylene carbonate and / or methyltrifluoroethyl carbonate.
[0052] In some embodiments of the present invention, the ether plasticizer is selected from at least one of ethylene glycol dimethyl ether and tetrahydrofuran.
[0053] In some embodiments of the present invention, the sulfone plasticizer is selected from at least one of dimethyl sulfone, diphenyl sulfone, sulfolane, and methylphenyl sulfone, and is preferably dimethyl sulfone.
[0054] In some embodiments of the present invention, the ionic liquid plasticizer is selected from one of 1-butyl-3-methylimidazolium hexafluorophosphate, N-methyl-N-propylpiperidinium bis(trifluoromethanesulfonyl)imide, and triethyl-n-butylammonium bis(trifluoromethanesulfonyl)imide, and is preferably 1-butyl-3-methylimidazolium hexafluorophosphate.
[0055] In some embodiments of the present invention, the mass ratio of the inelastic phase to the elastic phase in the polymer substrate is 1:1 - 100, preferably 1:4 - 10, more preferably 1:4.17, or 1:5, or 1:6.25, or 1:8.33.
[0056] In the present invention, the ratio of the elastic phase to the inelastic phase in the polymer substrate directly affects the comprehensive performance of the electrolyte. The elastic phase provides flexibility and interfacial compatibility, can adapt to volume changes during charge and discharge, and reduce interfacial impedance. However, too much elastic phase may lead to insufficient mechanical strength; while the inelastic phase endows the electrolyte with mechanical strength and structural stability, inhibiting dendrite growth. However, too high a content of the inelastic phase may reduce flexibility and ion transport efficiency. Reasonably regulating the ratio of the two balances mechanical properties, electrochemical properties, and safety, and optimizes the overall performance of the polymer electrolyte.
[0057] In some embodiments of the present invention, the mass ratio of the functional plasticizer to the polymer substrate is 1:5 - 100, preferably 1:5 - 10, more preferably 1:1.75, or 1.45, or 1:2.
[0058] In the present invention, too much amount of the functional plasticizer may damage the mechanical properties of the electrolyte, make it difficult to inhibit dendrite growth, and additionally increase the weight and volume of the battery, reducing the battery energy density; too little amount of the functional plasticizer cannot achieve the best effect.
[0059] In some embodiments of the present invention, the mass ratio of the metal ion salt in the superionic conductor material to the polymer substrate is 1:1 - 20, preferably 1:1 - 5, more preferably 1.455, or 1:3.7.
[0060] In some embodiments of the present invention, the metal ion salt in the superionic conductor material is selected from at least one of lithium sulfate, lithium nitrate, lithium chloride, lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, zinc sulfate, zinc nitrate, zinc chloride, zinc bis(fluorosulfonyl)imide, sodium sulfate, sodium nitrate, sodium chloride, sodium hexafluorophosphate, potassium sulfate, potassium nitrate, potassium chloride, and potassium bis(fluorosulfonyl)imide.
[0061] The second aspect of the present invention provides a method for preparing the superionic conductor material according to the first aspect, characterized in that the method is selected from at least one of electrospinning, blending, and in-situ spraying. The specific method depends on the structure of the superionic conductor material to be prepared.
[0062] The third aspect of the present invention provides the application of the superionic conductor material according to the first aspect in the preparation of metal batteries, secondary ion batteries, flexible batteries, capacitors, or hybrid energy storage devices as separators, solid electrolytes, or binders.
[0063] The fourth aspect of the present invention provides a solid electrolyte membrane made of the superionic conductor material according to the first aspect.
[0064] In some embodiments of the present invention, the thickness of the solid electrolyte membrane is 10 - 200 μm, the room temperature ionic conductivity is between 1×10 -5 -1×10 -2 S·cm -1 , the tensile strength is between 1 - 100 MPa, the elongation at break is between 50 - 1000%, the elastic modulus is 1 - 200 MPa, and the puncture strength is 1 - 10 N.
[0065] The fifth aspect of the present invention provides a lithium battery including the solid electrolyte membrane according to the fourth aspect.
[0066] In some embodiments of the present invention, the symmetric lithium battery of the solid electrolyte membrane has a cycle time of 300 - 3000 h, an overpotential of 20 - 100 mV, the number of full cell cycles is 100 - 1000 cycles, the specific capacity is 50 - 150 mAh g -1 , and the energy density is 100 - 500 Wh kg -1 .
[0067] The battery assembled with the prepared solid electrolyte membrane has a lower overpotential, a higher specific capacity, and excellent cycle performance. The prepared solid electrolyte membrane can be recycled and reused multiple times, and the performance of the battery assembled for the second time is still excellent compared to the performance of the first assembly.
[0068] The present invention will be described in detail below through examples.
[0069] For those without specific conditions noted in the following examples and comparative examples, they are carried out according to conventional conditions or the conditions recommended by the manufacturer. For reagents or instruments without the manufacturer noted, they are all conventional products that can be obtained through commercial channels.
[0070] Material source:
[0071] Thermoplastic polyurethane elastomer: Purchased from Shandong Yousuo Chemical Technology Co., Ltd., model: BTE-75A, analytical pure AR;
[0072] Polybutadiene rubber: Purchased from Aladdin Reagent Co., Ltd., analytical pure AR, weight average molecular weight Mw 200000 - 300000;
[0073] Butadiene: Purchased from Aladdin Reagent Co., Ltd., analytical pure AR, molecular weight 54.09;
[0074] Polytetrahydrofuran: Purchased from Aladdin Reagent Co., Ltd., analytical pure AR, weight average molecular weight Mw ~ 2900;
[0075] Hexamethylene diisocyanate: Purchased from Aladdin Reagent Co., Ltd., analytical pure AR, molecular weight 168.19;
[0076] Dibutyltin dilaurate: Purchased from Aladdin Reagent Co., Ltd., analytical pure AR, molecular weight 631.56;
[0077] Polyvinylidene fluoride - hexafluoropropylene: Purchased from GISMA-ALDRICH Co., analytical pure AR, weight average molecular weight Mw ~ 455000;
[0078] The lithium-doped basic calcium phosphate material is prepared by the following method:
[0079] Weigh 0.331 g of anhydrous calcium chloride and dissolve it in 40 mL of water, and 4.8 g of sodium oleate and dissolve it in 50 mL of water. After stirring until dissolved respectively, mix and stir for 1 h; adjust the pH to 10, add 50 mL of a solution containing 0.56 g of sodium dihydrogen phosphate, mix and stir for 30 min, and then add 0.133 g of lithium nitrate. After stirring for 1 h, a precursor solution is obtained: Load the precursor solution into a microwave hydrothermal reaction kettle, maintain it at 200 °C for 4 h, cool the reaction product to room temperature, wash it with water and alcohol, disperse it in water, and after washing and suction filtration, dry it at 60 °C for 12 h to obtain lithium-doped basic calcium phosphate;
[0080] Methyl trifluoroethyl carbonate: Purchased from Aladdin Reagent Co., Ltd., analytical pure AR, molecular weight 158.07.
[0081] Example 1
[0082] This example is used to illustrate the preparation of a recyclable elastic superionic conductor material. A thermoplastic polyurethane elastomer is used as the elastic phase and poly(vinylidene fluoride - hexafluoropropylene) as the inelastic phase to obtain a superionic conductor material with a symmetric multilayer structure.
[0083] (1) Weigh 2 g of thermoplastic polyurethane elastomer and dissolve it in 8 mL of N,N - dimethylformamide. Stir at 70 °C for 12 h until dissolved. Cast a 250 - μm - thick solution on a glass plate and dry it outdoors for 12 h to obtain an elastic phase material layer.
[0084] (2) Weigh 0.2 g of poly(vinylidene fluoride - hexafluoropropylene) and dissolve it in 5 mL of acetone. Stir for 12 h until dissolved, then add 0.11 g of lithium bis(trifluoromethanesulfonyl)imide and stir for 4 h to obtain an inelastic phase solution.
[0085] (3) Pre - place the dried elastic phase material layer on a 60 °C hot stage. Take 2.5 mL of the inelastic phase solution in the funnel of an air - type spray gun and in - situ spray it onto both surfaces of the elastic phase material layer. Dry it at 60 °C in a vacuum environment for 30 min to obtain a symmetric multilayer polymer substrate. Immerse the symmetric multilayer polymer substrate in a methyl(trifluoroethyl)carbonate solution containing 1 M lithium bis(trifluoromethanesulfonyl)imide to obtain a superionic conductor material.
[0086] In the prepared superionic conductor material, the mass ratio of the inelastic phase to the elastic phase is 1:5; the mass ratio of methyl(trifluoroethyl)carbonate to the polymer substrate is 1:1.75; the mass ratio of lithium bis(trifluoromethanesulfonyl)imide to the polymer substrate is 1:4.55.
[0087] Test results:
[0088] The thickness of the superionic conductor material measured by a thickness gauge is 76 μm, where the thickness of the inelastic phase material layer is 8 μm and the thickness of the elastic phase material layer is 60 μm.
[0089] The cross - section of the superionic conductor material was tested by scanning electron microscopy, and its thickness is 76 μm, as Figure 1 shown.
[0090] The alternating current impedance of the superionic conductor material at different temperatures was tested. It can be calculated that its ionic conductivity at room temperature is 1.53×10 -3 S cm -1 , and the conductor conforms to the Arrhenius law. The higher the temperature, the higher the ionic conductivity, as Figure 2 shown.
[0091] The stress - strain test of the material shows that its tensile strength is 8.8 MPa and the elongation at break is 240%, as Figure 3 shown.
[0092] The nanoindentation test of the material shows that its elastic modulus is 12.52 MPa, as Figure 4 shown.
[0093] The puncture test of the material shows that its puncture strength is 3.4 N, as Figure 5 shown.
[0094] The assembled symmetric battery is tested and can be cycled stably for 2700 h with an overpotential of 23 mV, as Figure 6 shown.
[0095] The assembled full battery is tested and can be cycled stably for 550 cycles, with a high specific capacity of 125 mAh g -1 and an energy density reaching 350 Wh kg -1 , as Figure 7 shown.
[0096] The room-temperature ionic conductivities of the secondary recycled superionic conductor materials are 1.10×10 -3 S cm -1 , as Figure 8 shown. The assembled symmetric battery and full battery are tested. As Figure 9 , 10 shown, the symmetric battery can be cycled stably for 1190 h, and the full battery can be cycled stably for 200 cycles, with a specific capacity of 105 mAh g -1 .
[0097] Example 2
[0098] The operating conditions are the same as those in Example 1, except that in step (3), 1 mL of the inelastic phase solution is taken for in-situ spraying.
[0099] In the prepared superionic conductor material, the mass ratio of the inelastic phase to the elastic phase is 1:10; the mass ratio of methyltrifluoroethyl carbonate to the polymer substrate is 1:1.45; the mass ratio of lithium bis(trifluoromethanesulfonyl)imide to the polymer substrate is 1:3.7.
[0100] The thickness of the superionic conductor material is measured by a thickness gauge to be 68 μm, where the thickness of the inelastic phase material layer is 4 μm and the thickness of the elastic phase material layer is 60 μm.
[0101] Example 3
[0102] The operating conditions are the same as those in Example 1, except that in step (1), an elastic phase solution with a thickness of 500 μm is cast on a glass plate.
[0103] In the prepared superionic conductor material, the mass ratio of the inelastic phase to the elastic phase is 1:10; the mass ratio of methyltrifluoroethyl carbonate to the polymer substrate is 1:2; the mass ratio of lithium bis(trifluoromethanesulfonyl)imide to the polymer substrate is 1:5.
[0104] The thickness of the superionic conductor material is measured by a thickness gauge to be 135 μm, where the thickness of the inelastic phase is 7.5 μm and the thickness of the elastic phase is 120 μm.
[0105] Example 4
[0106] This example is used to illustrate the preparation of a recyclable elastic superionic conductor material. A superionic conductor material with a symmetric multilayer structure is obtained using thermoplastic polyurethane elastomer as the elastic phase and lithium-doped basic calcium phosphate as the inelastic phase.
[0107] (1) Weigh 2 g of thermoplastic polyurethane elastomer and dissolve it in 8 mL of N,N-dimethylformamide. Stir at 70 °C for 12 h until dissolved, then add 1 g of a methyltrifluoroethyl carbonate solution of 1 M lithium bis(trifluoromethanesulfonyl)imide and stir for 4 h. Cast a 250-μm-thick solution on a glass plate and dry it outdoors for 12 h to obtain an elastic phase material layer;
[0108] (2) Weigh 0.2 g of lithium-doped basic calcium phosphate powder and dissolve it in 5 mL of deionized water. Stir for 12 h until homogeneous to obtain an inelastic phase solution;
[0109] (3) Use a scraper to evenly coat the 50-μm-thick inelastic phase solution on both surfaces of the elastic phase material layer, and dry it at 60 °C for 30 min in a vacuum environment to obtain a superionic conductor material with a symmetric multilayer structure.
[0110] In the prepared superionic conductor material, the mass ratio of the inelastic phase to the elastic phase is 1:5; the mass ratio of methyltrifluoroethyl carbonate to the polymer substrate is 1:1.75; the mass ratio of lithium bis(trifluoromethanesulfonyl)imide to the polymer substrate is 1:4.55.
[0111] The thickness of the superionic conductor material is measured by a thickness gauge to be 70 μm, where the thickness of the inelastic phase material layer is 5 μm and the thickness of the elastic phase material layer is 60 μm.
[0112] Example 5
[0113] The operating conditions are the same as in Example 1, except that in step (1), an equal mass of polybutadiene rubber is used instead of thermoplastic polyurethane elastomer.
[0114] In the prepared superionic conductor material, the mass ratio of the inelastic phase to the elastic phase is 1:5; the mass ratio of methyltrifluoroethyl carbonate to the polymer substrate is 1:1.75; the mass ratio of lithium bis(trifluoromethanesulfonyl)imide to the polymer substrate is 1:4.55.
[0115] The thickness of the superionic conductor material measured by a thickness gauge is 73 μm, where the thickness of the inelastic phase is 6.5 μm and the thickness of the elastic phase is 60 μm.
[0116] Example 6
[0117] This example is used to illustrate the preparation of a recyclable elastic superionic conductor material. Two monomers of polyurethane, polytetrahydrofuran and hexamethylene diisocyanate, and the catalyst dibutyltin dilaurate are used to synthesize the elastic phase, and polyvinylidene fluoride - hexafluoropropylene is used as the inelastic phase to obtain a superionic conductor material with a coaxial nanofiber network structure.
[0118] (1) Dissolve 0.15 g of polyvinylidene fluoride - hexafluoropropylene and 0.05 g of dibutyltin dilaurate in 10 mL of N,N - dimethylformamide, and stir for 12 h as the precursor solution for electrospinning; the working voltage during electrospinning is 20 kV, the flow rate is 16 cm, and the collection distance is 0.6 mL h -1 , the spinning temperature is 25 °C, and the relative humidity is 40%; peel the electrospun fiber membrane from the A4 paper and dry it at 70 °C in a vacuum environment.
[0119] (2) Immerse the electrospun fiber membrane in a 15 mL cyclohexanone solution containing 0.625 g of polytetrahydrofuran and 62.5 μL of hexamethylene diisocyanate, soak it at 40 °C for 10 h to in - situ polymerize the two monomers on the electrospun fiber; after the reaction, dry the in - situ polymerized coaxial nanofibers at 80 °C for 12 h in a vacuum environment; impregnate the coaxial nanofiber network with a methyl trifluoroethyl carbonate solution containing 1 M lithium bis(trifluoromethanesulfonyl)imide to obtain a superionic conductor material.
[0120] In the prepared superionic conductor material, the mass ratio of the inelastic phase to the elastic phase is 1:4.17; the mass ratio of methyl trifluoroethyl carbonate to the polymer substrate is 1:1.75; the mass ratio of lithium bis(trifluoromethanesulfonyl)imide to the polymer substrate is 1:4.55.
[0121] Example 7
[0122] The operating conditions are the same as in Example 6, except that the butadiene monomer of polybutadiene rubber is used instead of the polytetrahydrofuran and hexamethylene diisocyanate monomers of polyurethane, the mass of the butadiene monomer is 0.625 g, the catalyst n - butyllithium is used instead of dibutyltin dilaurate with a mass of 0.002 g, and the solvent toluene is used instead of cyclohexanone.
[0123] In the prepared superionic conductor material, the mass ratio of the inelastic phase to the elastic phase is 1:4.17; the mass ratio of methyltrifluoroethyl carbonate to the polymer substrate is 1:1.75; the mass ratio of lithium bis(trifluoromethanesulfonyl)imide to the polymer substrate is 1:4.55.
[0124] Example 8
[0125] The operating conditions are the same as in Example 6, except that lithium-doped basic calcium phosphate is used instead of poly(vinylidene fluoride-hexafluoropropylene).
[0126] In the prepared superionic conductor material, the mass ratio of the inelastic phase to the elastic phase is 1:4.17; the mass ratio of methyltrifluoroethyl carbonate to the polymer substrate is 1:1.75; the mass ratio of lithium bis(trifluoromethanesulfonyl)imide to the polymer substrate is 1:4.55.
[0127] Example 9
[0128] The operating conditions are the same as in Example 7, except that lithium-doped basic calcium phosphate is used instead of poly(vinylidene fluoride-hexafluoropropylene).
[0129] In the prepared superionic conductor material, the mass ratio of the inelastic phase to the elastic phase is 1:4.17; the mass ratio of methyltrifluoroethyl carbonate to the polymer substrate is 1:1.75; the mass ratio of lithium bis(trifluoromethanesulfonyl)imide to the polymer substrate is 1:4.55.
[0130] Example 10
[0131] This example is used to illustrate the preparation of a recyclable elastic superionic conductor material. Using thermoplastic polyurethane elastomer as the elastic phase and lithium-doped basic calcium phosphate as the inelastic phase, a superionic conductor material with a 3D crosslinked network structure is obtained.
[0132] (1) Dissolve 1 g of lithium-doped basic calcium phosphate powder in 5 mL of ethanol, and dissolve 5 g of TPU particles in 10 mL of N,N-dimethylformamide;
[0133] (2) Load the lithium-doped basic calcium phosphate spinning solution into the syringe of an electrospinning machine, with a voltage of 15 kV, a pushing speed of 1 mL h -1 , a receiving distance of 15 cm, collect the lithium-doped basic calcium phosphate fiber membrane on an aluminum foil receiver, and dry it at 80 °C for 2 h in a vacuum environment;
[0134] (3) Load the TPU spinning solution into the syringe of the electrospinning machine; set the spinning parameters: voltage 20 kV, pushing speed 1.5 mL h -1 , a receiving distance of 20 cm, collect the thermoplastic polyurethane fiber membrane on an aluminum foil receiver, and dry it at 60 °C for 2 h in a vacuum environment;
[0135] (4) Alternately stack the lithium-doped basic calcium phosphate fiber membrane and the thermoplastic polyurethane fiber membrane, then place them in a hot press and hot press at 120 °C and a pressure of 5 MPa for 10 min; after cooling to room temperature, a 3D cross-linked network is formed; impregnate the polymer substrate with a methyl trifluoroethyl carbonate solution containing 1 M lithium bis(trifluoromethanesulfonyl)imide to obtain a superionic conductor material with a 3D cross-linked network structure.
[0136] In the prepared superionic conductor material, the mass ratio of the inelastic phase to the elastic phase is 1:5; the mass ratio of methyl trifluoroethyl carbonate to the polymer substrate is 1:1.75; the mass ratio of lithium bis(trifluoromethanesulfonyl)imide to the polymer substrate is 1:4.55.
[0137] Example 11
[0138] The operating conditions are the same as those in Example 7, except that the mass of butadiene monomer is 1.25 g and the mass of the catalyst n-butyllithium is 0.004 g.
[0139] In the prepared superionic conductor material, the mass ratio of the inelastic phase to the elastic phase is 1:8.33; the mass ratio of methyl trifluoroethyl carbonate to the polymer substrate is 1:2; the mass ratio of lithium bis(trifluoromethanesulfonyl)imide to the polymer substrate is 1:5.
[0140] Example 12
[0141] The operating conditions are the same as those in Example 9, except that the mass of lithium-doped basic calcium phosphate is 0.1 g.
[0142] In the prepared superionic conductor material, the mass ratio of the inelastic phase to the elastic phase is 1:6.25; the mass ratio of methyl trifluoroethyl carbonate to the polymer substrate is 1:1.45; the mass ratio of lithium bis(trifluoromethanesulfonyl)imide to the polymer substrate is 1:3.7.
[0143] Comparative Example 1
[0144] The operating conditions are the same as those in Example 1, except that poly(vinylidene fluoride - hexafluoropropylene) is not sprayed.
[0145] Comparative Example 2
[0146] Cut a copper foil of 10×10 cm 2 and place it on a 60 °C hot stage; take 2.5 mL of the inelastic phase solution prepared in step (2) of Example 1 and put it in the funnel of an airbrush, and spray it evenly on the copper foil to obtain a poly(vinylidene fluoride - hexafluoropropylene) electrolyte.
[0147] Comparative Example 3
[0148] Weigh 1 g of thermoplastic polyurethane elastomer and 0.2 g of poly(vinylidene fluoride - hexafluoropropylene), dissolve them in 10 mL of N,N - dimethylformamide, and stir at 70 °C for 12 h until dissolved; then add 1 g of lithium bis(trifluoromethanesulfonyl)imide, stir for 4 h, cast a 250 - μm - thick solution on a glass plate, and dry it outdoors for 12 h to obtain a polymer substrate; impregnate it with a methyltrifluoroethyl carbonate solution containing 1 M lithium bis(trifluoromethanesulfonyl)imide to obtain a superionic conductor material.
[0149] Test Example 1
[0150] Perform basic mechanical and electrochemical tests on the superionic conductor materials prepared in Examples 1 - 10 and Comparative Examples 1 - 3.
[0151] Room - temperature ionic conductivity test: Clamp the superionic conductor material between two stainless - steel gaskets, connect an electrochemical workstation to conduct an alternating - current impedance test, with a frequency range of 1 MHz - 0.1 Hz.
[0152] Thickness test: Place the superionic conductor material between two weighing papers and measure the thickness using a thickness gauge.
[0153] Tensile strength and elongation at break test: The tensile speed is 5 mm / min -1 , cut the sample into dumbbell - shaped specimens, and input the thickness, width, and length of the specimen into the working area.
[0154] Puncture test: Fix the sample on the sample stage and ensure the surface is flat, select a suitable puncture needle and fixture, set the test parameters such as puncture speed, maximum load, and test range, and pierce the sample at a constant speed.
[0155] Nano - indentation test: Fix the sample on the sample stage and ensure the surface is flat, set the test parameters such as maximum load, loading rate, and holding time, and the indenter slowly contacts the sample surface and applies a load.
[0156] The experimental results are shown in Table 1.
[0157] Table 1
[0158]
[0159]
[0160] Test Example 2
[0161] Cut the superionic conductor materials prepared in Examples 1 - 10 and Comparative Examples 1 - 3 into circular discs with a diameter of 12 cm, and assemble them with lithium metal to form Li||Li symmetric batteries (the structure is lithium metal|electrolyte|lithium metal), where the diameter of the lithium metal electrode is 9 mm, and the button - type symmetric battery model is CR2032. At a current density of 0.1 mA / cm -2Current density, 0.1 mAh cm -2 The capacity was tested under symmetric cell conditions at 30 °C.
[0162] For the LFP cathode, N-methylpyrrolidone was used as the solvent. The corresponding chemicals were weighed according to the mass ratio of LFP:PVDF:acetylene black = 8:1:1, ground evenly in a mortar, coated on carbon-coated aluminum foil with a diameter of 10 mm, and dried in a vacuum oven at 120 °C for 12 h. After taking it out, it was used as the cathode. The all-solid-state batteries of Li||SPE||LFP were assembled with the superionic conductor materials obtained in Examples 1-10 and Comparative Examples 1-4. The current density was selected as 0.5 C, and the battery voltage window was selected as 2.5 - 4.2 V. The full-cell long-cycle test was carried out at 30 °C.
[0163] The whole process of assembling the battery needs to be carried out in a glove box filled with argon.
[0164] The test results are shown in Table 2.
[0165] Table 2
[0166]
[0167]
[0168] Test Example 3
[0169] Secondary recycling: The cycled symmetric cell was disassembled, the electrolyte was taken out, and put into an acetone / N,N-dimethylformamide / cyclohexanone / toluene solution. The elastic phase and the non-elastic phase were separated by using the difference in solubility. Then, secondary repeated preparation was carried out.
[0170] Table 3
[0171]
[0172]
[0173] In the examples of the present invention, recyclable elastic superionic conductor materials with three different structures, namely a symmetric multilayer structure, a coaxial nanofiber network structure, and a 3D crosslinked network structure, are used, which are composed of an elastic phase (thermoplastic polyurethane elastomer, polybutadiene rubber) and a non-elastic phase (polyvinylidene fluoride hexafluoropropylene, lithium-doped basic calcium phosphate).
[0174] Mechanical property tests such as stress-strain, nanoindentation, and puncture experiments show that the superionic conductor material (Example 1) composed of thermoplastic polyurethane and poly(vinylidene fluoride - hexafluoropropylene) with a symmetric multilayer structure has more excellent tensile strength (8.8 MPa), elastic modulus (12.52 MPa), and puncture strength (3.4 N). A low proportion of the inelastic phase (Examples 2 and 3) causes an imbalance in the elastic and mechanical strength properties of the superionic conductor material, resulting in a decline in mechanical properties. When the elastic phase is replaced with polybutadiene rubber (Example 5), the mechanical properties are not better than those of Example 1 because of the poor tensile, puncture, and elastic properties of polybutadiene rubber itself, which makes the mechanical properties of the superionic conductor material also poor. When the inelastic phase is replaced with lithium-doped basic calcium phosphate (Example 4), due to the introduction of inorganic fillers, the mechanical properties are also better than those of Example 5, but still not better than those of Example 1. When using thermoplastic polyurethane and poly(vinylidene fluoride - hexafluoropropylene) to form coaxial nanofibers (Example 6) or a 3D crosslinked network (Example 10), the tensile strength and puncture performance are close to those of Example 1, but the elastic modulus is generally still poor. Based on Example 6, when the elastic phase is replaced with polybutadiene rubber (Example 7) or / and the inelastic phase is replaced with lithium-doped basic calcium phosphate (Examples 8 and 9), and when deviating from the ratio of inelastic phase:elastic phase = 1:4.17 (Examples 11 and 12), the mechanical property laws similar to those of the multilayer superionic conductor are all shown.
[0175] Electrochemical property tests such as room-temperature ionic conductivity, symmetric cells, and full cells show that the room-temperature ionic conductivity of the superionic conductor material (Example 1) composed of thermoplastic polyurethane and poly(vinylidene fluoride - hexafluoropropylene) with a symmetric multilayer structure is 1.53×10 -3 S cm -1 . The assembled symmetric cell can stably cycle >2700 h at a current density of 0.1 mA cm -2 and a capacity of 0.1 mAh cm -2 , with a small overpotential of 23 mV. The assembled lithium iron phosphate full cell can stably cycle 550 times at a current density of 0.5 C, and the specific capacity is still 125 mAh g -1 , and the energy density can reach 350 Wh kg -1 , showing extremely excellent battery cycling performance. The electrochemical property laws of the remaining examples are almost consistent with the mechanical property laws because the ion transport properties of the elastic phase polybutadiene rubber and the inelastic phase lithium-doped basic calcium phosphate are weaker than those of thermoplastic polyurethane and poly(vinylidene fluoride - hexafluoropropylene).
[0176] After the secondary recycling of the superionic conductor material of the examples, the ionic conductivity and the cycling performance of the symmetric cells and full cells all decrease to a certain extent compared with before recycling, but the overall electrochemical performance of Example 1 is still relatively excellent.
[0177] It can be seen from the results in Tables 1 - 3 that a polymer substrate with a special structure is composed of polymers with excellent intrinsic elastic properties and polymer / inorganic materials with strong mechanical properties (such as thermoplastic polyurethane elastomer, polybutadiene rubber; polyvinylidene fluoride - hexafluoropropylene, lithium - doped basic calcium phosphate). Different components play their advantages specifically, which can provide excellent mechanical properties and elastic properties to the superionic conductor and effectively maintain the stability of the electrode / electrolyte interface. The introduced functional plasticizer also provides a high - speed channel for ion transport, resulting in a superionic conductor material with high elasticity, high mechanical strength and high ionic conductivity. The batteries assembled with this solid electrolyte all have a low over - potential, a high energy density and excellent cycling performance. At the same time, due to the special structure design of the polymer substrate, it can be recycled, has good resource recycling ability and environmental friendliness, and after recycling treatment, the performance of the assembled battery is still excellent and the capacity has no obvious attenuation.
[0178] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited thereto. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solutions of the present invention, including any other suitable combination of each technical feature. These simple modifications and combinations should also be regarded as the content disclosed by the present invention and all fall within the protection scope of the present invention.
Claims
1. A recyclable elastic superionic conductor material, characterized in that: The superionic conductor material comprises a polymer substrate and a functional plasticizer doped in the polymer substrate; The polymer substrate includes an elastic phase and an inelastic phase, and the elastic phase and the inelastic phase are independent of each other in structure.
2. The superionic conductor material according to claim 1, wherein: The structure of the superionic conductor material is selected from at least one of a symmetrical or asymmetrical multilayer structure, a coaxial nanofiber network structure, and a 3D cross-linked network structure; Preferably, in the symmetrical or asymmetrical multilayer structure, the elastic phase and the inelastic phase are located in different layers, and preferably, the inelastic phase material layer is arranged on both sides of the elastic phase material layer; Preferably, the coaxial nanofiber network structure is a fiber network formed in a non-elastic phase and coated with an elastic phase material; Preferably, the 3D cross-linked network structure is formed by hot pressing alternately stacked non-elastic phase fiber networks and elastic phase fiber networks.
3. The superionic conductor material according to claim 1 or 2, wherein: The elastic phase is selected from at least one of a thermoplastic elastomer and a thermosetting elastomer; Preferably, the thermoplastic elastomer is selected from at least one of styrene-isoprene block copolymer, vulcanized rubber, thermoplastic polyurethane elastomer, ethylene-octene copolymer, butylene terephthalate, polyamide elastomer and polyvinyl chloride-based thermoplastic elastomer, preferably vulcanized rubber and / or thermoplastic polyurethane elastomer; Preferably, the thermosetting elastomer is selected from at least one of natural rubber, isoprene rubber, polybutadiene rubber, styrene-butadiene rubber, nitrile rubber and chloroprene rubber, preferably at least one of polybutadiene rubber, styrene-butadiene rubber and nitrile rubber.
4. The superionic conductor material according to any one of claims 1 to 3, wherein The non-elastic phase is selected from at least one of a traditional inorganic filler, a novel inorganic filler and a common non-elastic polymer; Preferably, the conventional inorganic filler is selected from at least one of silica, alumina, titania, zirconium dioxide, LLZO, LLTO, LATP and LGPS, preferably at least one of silica, alumina, titania, zirconium dioxide and LLZO; Preferably, the novel inorganic filler is selected from at least one of graphene oxide, carbon quantum dots, lithium-doped basic calcium phosphate, ZIF-90-NH2 and CN@LLZTO, preferably graphene oxide and / or lithium-doped basic calcium phosphate; Preferably, the common non-elastic polymer is selected from at least one of polyethylene oxide, polyacrylonitrile, polyethylene carbonate, polymethyl methacrylate and polyvinylidene fluoride, preferably polyethylene oxide and / or polyvinylidene fluoride-hexafluoropropylene.
5. The superionic conductor material according to any one of claims 1 to 4, wherein The functional plasticizer is selected from at least one of carbonate plasticizers, ether plasticizers, sulfone plasticizers and ionic liquid plasticizers; Preferably, the carbonate plasticizer is selected from at least one of ethylene carbonate, propylene carbonate, methyl trifluoroethyl carbonate, dimethyl carbonate and diethyl carbonate, preferably ethylene carbonate and / or methyl trifluoroethyl carbonate; Preferably, the ether plasticizer is selected from at least one of ethylene glycol dimethyl ether and tetrahydrofuran; Preferably, the sulfone plasticizer is selected from at least one of dimethyl sulfone, diphenyl sulfone, cyclopentane and methyl phenyl sulfone, preferably dimethyl sulfone; Preferably, the ionic liquid plasticizer is selected from one of 1-butyl-3-methylimidazolium hexafluorophosphate, N-methyl-N-propylpiperidinium bis(trifluoromethanesulfonyl)imide and triethyl-n-butylammonium bis(trifluoromethanesulfonyl)imide, preferably 1-butyl-3-methylimidazolium hexafluorophosphate.
6. The superionic conductor material according to any one of claims 1 to 5, wherein The mass ratio of the non-elastic phase to the elastic phase in the polymer substrate is 1:1-100, preferably 1:4-10, more preferably 1:4.17, or 1:5; Preferably, the mass ratio of the functional plasticizer to the polymer substrate is 1:5-100, preferably 1:5-10, and more preferably 1:1.75; Preferably, the mass ratio of the metal ion salt in the superionic conductor material to the polymer substrate is 1:1-20, preferably 1:1-5, and more preferably 1.455; Preferably, the metal ion salt in the superionic conductor material is selected from at least one of lithium sulfate, lithium nitrate, lithium chloride, lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, zinc sulfate, zinc nitrate, zinc chloride, zinc bis(fluoromethanesulfonyl)imide, sodium sulfate, sodium nitrate, sodium chloride, sodium hexafluorophosphate, potassium sulfate, potassium nitrate, potassium chloride and potassium bis(fluoromethanesulfonyl)imide.
7. A method for preparing a superionic conductor material according to any one of claims 1 to 6, characterized in that: The method is selected from at least one of an electrospinning method, a blending method and an in-situ spraying method.
8. Use of the superionic conductor material according to any one of claims 1 to 6 as a separator, solid electrolyte or binder in the preparation of metal batteries, secondary ion batteries, flexible batteries, capacitors or hybrid energy storage devices.
9. A solid electrolyte membrane made of the superionic conductor material according to any one of claims 1 to 6; Preferably, the thickness of the solid electrolyte membrane is 10-200 μm, and the room temperature ionic conductivity is 1×10 -5 -1×10 -2 S cm -1 , tensile strength is 1-100MPa, elongation at break is 50-1000%, elastic modulus is 1-200MPa, and puncture strength is 1-10N.
10. A lithium battery comprising the solid electrolyte membrane according to claim 9; Preferably, the symmetrical lithium battery with the solid electrolyte membrane has a cycle time of 300-3000 h, an overpotential of 20-100 mV, a full battery cycle number of 100-1000 cycles, and a specific capacity of 50-150 mAh g -1 , energy density is 100-500Wh kg -1 .